2016
DOI: 10.1002/2016jc011818
|View full text |Cite
|
Sign up to set email alerts
|

Budget of organic carbon in the North‐Western Mediterranean open sea over the period 2004–2008 using 3‐D coupled physical‐biogeochemical modeling

Abstract: A 3‐D hydrodynamic‐biogeochemical coupled model has been used to estimate a budget of organic carbon and its interannual variability over the 5 year period 2004–2008 in the North‐Western Mediterranean Open Sea (NWMOS). The comparison of its results with in situ and satellite observations reveals that the timing and the magnitude of the convection and bloom processes during the study period, marked by contrasted atmospheric conditions, are reasonably well reproduced by the model. Model outputs show that the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 103 publications
2
59
0
1
Order By: Relevance
“…Although some of the exported material will be injected back into the surface layer during the next convection event, a consequence of deep circulation is horizontal transport of organic matter toward the Algerian basin. In this context, our results are in agreement with the quantification of Ulses et al (), who found the transfer to the Algerian subbasin deep waters (100 m seabed) was equivalent to 53% of the OC exported below 100 m in the convective region (337 × 10 4 tC yr −1 ). An additional 165 × 10 4 tC yr −1 was conveyed in the first 100 m. These advective processes are thought to create a coupling between the three regions, and their consequences, notably on carbon sequestration deserve more attention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although some of the exported material will be injected back into the surface layer during the next convection event, a consequence of deep circulation is horizontal transport of organic matter toward the Algerian basin. In this context, our results are in agreement with the quantification of Ulses et al (), who found the transfer to the Algerian subbasin deep waters (100 m seabed) was equivalent to 53% of the OC exported below 100 m in the convective region (337 × 10 4 tC yr −1 ). An additional 165 × 10 4 tC yr −1 was conveyed in the first 100 m. These advective processes are thought to create a coupling between the three regions, and their consequences, notably on carbon sequestration deserve more attention.…”
Section: Resultsmentioning
confidence: 99%
“…Observations of the DeWEx Leg1 campaign in February 2013 showed the presence of phytoplankton at depths > 2,000 m, at concentrations of 0.16 mg m −3 (Kessouri et al, ). These observations suggest that vertical mixing and advection are responsible for the presence of organic carbon, including light cells and detritus, in deep layers, as observed by Giering et al () in the Iceland Basin, and modeled by Ulses et al () in the northwestern Mediterranean. It is likely that a fraction of the exported matter observed in deep waters during the winter of 2012/2013 was permanently trapped when mixing stopped.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[]. This coupled hydrodynamical‐biogeochemical tool was also used to study the impact of interannual variability and long‐term evolution of atmospheric and oceanic conditions, in particular deep convection, on the NWMS pelagic planktonic ecosystem and associated carbon cycle [ Herrmann et al ., ; Ulses et al ., ]. Those studies showed that our coupled model represents realistically NWMS ocean dynamics, in particular deep convection, as well as the interactions between dynamics and biogeochemistry.…”
Section: Methods and Toolsmentioning
confidence: 99%